Existence and uniqueness of solutions of nonlocal problems for hyperbolic equation uxt=F(x, t, u, ux). (1990) - Byszewski, L.
Abstract : The aim of the paper is to give two theorems about existence and uniqueness of continuous solutions for hyperbolic nonlinear differential problems with nonlocal conditions in bounded and unbounded domains. The results obtained in this paper can be applied in the theory of elasticity with better effect than analogous known results with classical initial conditions.